Respons Pertumbuhan dan Hasil Tanaman Sorgum (Sorghum bicolor L. Moench) Terhadap Pemberian Pupuk Bokashi Kotoran Sapi dan Waktu Penyiangan Gulma di Tanah Rawa Lebak: Growth Responses and Production of Sorghum (Sorghum bicolor L. moench) to Cow Manure Fertilizer and Weeding Time at Swamp Land - Meci Yuniastuti Rahma; Sri Hartati (Politeknik Negeri Lampung, 2022)
Data from the Directorate of Serelia Cultivation shows that Indonesia's sorghum production in the last 5 years has only increased slightly from 6,114 tons to 7,695 tons. The increase in domestic sorghum production needs special attention because Indonesia has great potential for sorghum development (Subagio and Aqil, 2013), therefore it is necessary to respond to the growth and production of sorghum (Sorghum Bicolor L. moench) plants to the application of cow dung bokashi fertilizer and weeding time in the Lebak swamp. This study aims to determine the response of growth and yield of sorghum plants. This research has been carried out by Lr. Karang sublime, Talang Putri Village, Plaju District, Palembang. The design used was a randomized block design (RAK) which was arranged in a factorial manner consisting of two factors, namely the weeding time factor (P) and the cow dung bokashi fertilizer dose factor (K). The treatment factor for weeding time consisted of 3 levels, namely P1 (7 DAP), P2 (14 DAP), P3 (21 DAP) and the dose treatment factor for cow dung bokashi fertilizer consisted of 3 levels, namely K1 (bovine bokashi fertilizer 100g per plant). K2 (bovine dung bokashi fertilizer 150g per plant), K3 (cow dung bokashi fertilizer 200g per plant), so there were 9 treatment combinations with 3 replications/group, where each treatment consisted of 27 plants with 4 sample plants. The variables observed in this study consisted of 1) plant height (cm), 2) flowering age (days), 3) fruit weight (g). The results showed that the treatment of weeding time for 14 days after planting and the application of 200g cow dung bokashi fertilizer per plant had a significant effect on all observed variables.